Relationship Between Metformin Use and Recurrence and Survival in Patients With Resected Stage III Colon Cancer Receiving Adjuvant Chemotherapy: Results From North Central Cancer Treatment Group N0147 (Alliance). (23rd November 2016) - Singh, Preet Paul; Shi, Qian; Foster, Nathan R.; Grothey, Axel; Nair, Suresh G.; Chan, Emily; Shields, Anthony F.; Goldberg, Richard M.; Gill, Sharlene; Kahlenberg, Morton S.; Sinicrope, Frank A.; Sargent, Daniel J.; et al.
Abstract : Background: Preclinical and epidemiological data suggest that metformin might have antineoplastic properties against colon cancer (CC). However, the effect of metformin use on patient survival in stage III CC after curative resection is unknown. The survival outcomes were comparable regardless of the duration of metformin use. Patients and Methods: Before randomization to FOLFOX (folinic acid, 5-fluorouracil, oxaliplatin) with or without cetuximab, 1, 958 patients with stage III CC enrolled in the N0147 study completed a questionnaire with information on diabetes mellitus (DM) and metformin use. Cox models were used to assess the association between metformin use and disease-free survival (DFS), overall survival (OS), and the time to recurrence (TTR), adjusting for clinical and/or pathological factors. Results: Of the 1, 958 patients, 1, 691 (86%) reported no history of DM, 115 reported DM with metformin use (6%), and 152 reported DM without metformin use (8%). The adjuvant treatment arms were pooled, because metformin use showed homogeneous effects on outcomes across the two arms. Among the patients with DM ( n = 267), DFS (adjusted hazard ratio [aHR], 0.90; 95% confidence interval [CI], 0.59–1.35; p = .60), OS (aHR, 0.99; 95% CI, 0.65–1.49; p = .95), and TTR (aHR, 0.87; 95% CI, 0.56–1.35; p = .53) were not different for the metformin users compared with the nonusers after adjusting for tumor and patient factors. The survival outcomes were comparable regardless of the duration of metformin use (<1, 1–5, 6–10, ≥11 years) before randomization ( p trend = .64 for DFS, p trend = .84 for OS, and p trend = .87 for TTR). No interaction effects were observed between metformin use and KRAS, BRAF mutation status, tumor site, T/N stage, gender, or age. Conclusions: Patients with stage III CC undergoing adjuvant chemotherapy who used metformin before the diagnosis of CC experienced DFS, OS, and TTR similar to those for non-DM patients and DM patients without metformin use. Abstract : Metformin might have antineoplastic properties against colon cancer (CC). Patients with stage III CC enrolled in the N0147 study completed a questionnaire regarding diabetes mellitus (DM) and metformin use. Patients with stage III CC undergoing adjuvant chemotherapy who used metformin before the diagnosis of CC experienced survival outcomes similar to those for non-DM patients and DM patients without metformin use.